Running Designs that Affect Calories Burned - Md Yusof, Zahayu; Misiran, Masnita; Ibrahim, Adyda (Universiti Pendidikan Sultan Idris, 2018)
Balanced between good diet and regular physical activity is among the important factors in avoiding unhealthy weight gain. Our objective in this study was to investigate the amount of calorie loss against a variety of running exercises. In this study, an experiment on running as a calorie burning physical activities was conducted. Two factors were selected, the distance, and the level of difficulties. The result and statistical analysis concluded that both factors play significant roles in burning calories, with distance as being the most significant factor. The findings also suggest that other than increasing the distance, choosing a hilly terrain when training can give more efficient calories burn. There is no interaction between distance and the level of difficulties. Individuals should plan their workout accordingly only after knowing how many calories they burned through each activity. For individual with aims to burn more calories, an increase in distance and a hilly terrain is more favorable